(untitled) (American Journal of Islam and Society, 2012)
It is a rare treat to find an English-language work of intellectual history by a scholar who is proficient in Arabic, Indonesian, and French – and thus capable of bringing together the Indonesian Islamicist Nurcholish Madjid (1939- 2005), the Egyptian philosopher Hasan Hanafi (1935-), and the French- Algerian Islamicist Mohamed Arkoun (1928-2010). Carool Kersten offers the first systematic treatment in English of these three figures’ thought and convincing arguments for why they not only deserve consideration together, but also why, when taken together, they represent a significant development in Islamic thought. Kersten argues that these three Islamic thinkers form part of “the first generation of Muslim thinkers reaching intellectual maturity in the postcolonial age” and are “representative of a new type of Muslim intellectual emerging in the 1960s” (p. xiv). Despite the enthusiastic language he associates with these “pioneers” and “trailblazers” (p. xvi), the author wisely takes care to draw attention to what these figures owe to earlier scholars and thinkers at many points. He also avoids overstated claims about how they either exemplify or hold great influence over their generation as a whole ...